Cloves syndrome vs. Klippel-Trenaunay syndrome: a case report - López-García , Diana (2024)
Vascular malformations represent a heterogeneous spectrum of lesions that often present a diagnostic and therapeutic challenge, thus requiring a high index of clinical suspicion to reach a definitive diagnosis. Cloves syndrome is a rare overgrowth disorder of genetic etiology associated with a somatic activating mutation in PIK3CA, which is part of the PI3KAkt-mTOR intracellular signaling pathway. Clinically, it is characterized by congenital lipomatous overgrowth of any part of the body (mainly the thorax), accompanied by vascular and lymphatic malformations, epidermal nevi and structural abnormalities of the skeletal system such as scoliosis and alterations in the spine. The current therapeutic cornerstone for this syndrome is therapy with rapamycin, an mTOR pathway inhibitor. On the other hand, Klippel-Trenaunay syndrome is a complex vascular condition associated with overgrowth due to somatic mutations in the PIK3CA gene, along with chromosomal translocations and alterations in the VG5Q vascular gene. It is clinically characterized by a classic triad consisting of hemihypertrophy of the soft tissues and bones of an extremity, cutaneous hemangiomas, and varicose veins in anatomically abnormal positions. The main distinguishing characteristics of this syndrome are the presence of slow-type vascular anomalies without significant arteriovenous fistulas compared to Cloves syndrome. In both cases, the presence of overlapping clinical characteristics related to overgrowth syndromes with alterations in the PIK3CA gene highlights the challenge of an accurate diagnosis.